THE RUSSIA’S BANKING SECTOR CREDIT POTENTIAL: CONDITIONS, AND GROWTH PROSPECTS - SERGEY ALEKSANDROVICH Andryushin (Мир новой экономики)
Retraction.The paper analyses the Russia’s banking sector credit potential, and the Bank of Russia policies, aiming to surge lending of industrial firms in middle range period.